BITUMINIZED CEMENT CONCRETE FOR HIGHWAYS (Spectrum Journal of Innovation, Reforms and Development, 2024)
The article considers the issue of increasing the strength and deformability of cement–concrete road surfaces by using an effective technological method - the introduction of bitumen emulsion into the concrete. The experimental data of the developed cement concrete with bitumen emulsion are presented, confirming the positive effect of bitumen emulsion on the performance properties of road concrete and increasing its strength and deformative properties.